Efficient environmental regulation: case studies of urban air pollution: Los Angeles, Mexico City, Cubatao, and Ankara - Levinson, Arik (IBRD Washington, D.C.US, 1992)
Reviews the economic principles on which policy choices should be based and considers how they may be applied in the real world. Examines four cities that continue to face serious air polution problems.